Physicians’ Examination and Referral Practices on Orthodontic Problems Among 6–12-Year-Old Children in Saudi Arabia - Alrejaye NS; Alnasser LA; Alsuliman AF; Alomran DK; Alshehri HH; Almalki MM; Alenazi SS; Bushnak IA; Abolfotouh MA (Dove Medical Press, 2023)
Najla S Alrejaye,1- 3 Lubna A Alnasser,2 Abdalaziz F Alsuliman,4 Dema Khalid Alomran,4 Hanan H Alshehri,3 Maram M Almalki,3 Suha S Alenazi,3 Ibraheem A Bushnak,2 Mostafa A Abolfotouh2 1Dental Health Services, King Abdulaziz Medical City/Ministry of National Guard Health Affairs, Riyadh, 11426, Saudi Arabia; 2King Abdullah International Medical Research Center/ King Saud bin Abdulaziz University for Health Sciences/ Ministry of National Guard Health Affairs, Riyadh, 14611, Saudi Arabia; 3College of Dentistry/ King Saud bin Abdulaziz University for Health Sciences/ Ministry of National Guard Health Affairs, Riyadh, 11426, Saudi Arabia; 4College of Dentistry/ King Saud University, Riyadh, 11451, Saudi ArabiaCorrespondence: Mostafa A Abolfotouh, King Abdullah International Medical Research Center/King Saud bin Abdulaziz University for Health Sciences/Ministry of National Guard Health Affairs, POB 22490, Riyadh, 11426, Saudi Arabia, Email mabolfotouh@gmail.comBackground: Physicians are more likely to examine children than dentists; thus, they may have a significant role in detecting oral and dentofacial problems. This study aimed to determine the rate and comprehensiveness of examinations, the rate and quality of referral practices, and the predictors of referral practice of physicians regarding orthodontic problems among children.Methods: In a multi-center cross-sectional study, a total of 518 physicians in Saudi Arabia were subjected to an e-questionnaire of four sections: (1) Physicians' demographic and work-related characteristics; (2) Physicians' comprehensiveness of oral and orthodontic examinations; (3) Physicians' referral practices to orthodontists and reasons considered for referral; and (4) Physicians' sources of orthodontic education. Logistic regression analysis was applied to identify the significant predictors of referral practice. The significance was set at p < 0.05.Results: Most physicians reported partial oral (78.5%) and orthodontic (72.2%) examinations, while the full examination was reported by only 12% and 2.5% of physicians, respectively. Referral to orthodontists was practiced by most of the physicians (83.8%), yet for the majority of them, the quality of referral was poor (40.3%) or fair (46.1%), with only 13.6% who practiced quality referral. Dental development issues (53.3%) and functional issues (51.5%) were reported as the main reasons for referral, followed by family/patient request (42.9%), dental alignment (42.5%), oral respiratory issues (32.4%), and finally jaw relation (26.1%). Referral practice was predicted by the comprehensive oral (OR = 2.37, p = 0.007) and orthodontic (OR = 4.26, p < 0.001) examinations, number of patients seen by the physician (OR = 1.58, p = 0.007), and level of training (OR = 1.88, p = 0.03).Conclusion: Although most physicians reported high rates of examination and referral practices on orthodontic problems among children in Saudi Arabia, only a small portion showed comprehensive examinations and quality referral practice. Including dental courses in medical curricula and improving oral and orthodontic examination guidelines for physicians are recommended.Keywords: dentofacial, dental development, malocclusion, pediatrics, orthodontists, multidisciplinary